INDIVIDUAL CHARACTERISTICS, MATERNAL KNOWLEDGE, ATTITUDE, AND PRACTICES IN WATER, SANITATION, AND HYGIENE USING SOCIO-ECOLOGICAL MODEL (STUDI KASUS: KABUPATEN PIDIE, ACEH) - Seicha Fathma, Syarifah
In developing countries, including Indonesia, a lack of sanitation serves a significant part in disease transmission. The family, particularly the mother, is responsible for providing duties related to water, sanitation, and hygiene. This is demonstrated by the fact that many people continue to open defecation free due to the low ownership of household latrines in Pidie. Mother is crucial in the family's management of clean water and sanitation, the process of analyzing the relationship between each variable using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of Smart-PLS 3.0 software. The mother is the primary manager of the family and is responsible for caring for the children, thus it seems to reason that she should be knowledgeable about water, sanitation, and hygiene. This research finds a significant positive relationship between individual characteristics (age, mother's educational level, marital status, mother's occupation, mother's monthly income, total family income, number of household heads in one household, and number of children under five ) and knowledge, attitude, and the mother's behavior in providing for the basic access of clean water, sanitation, and hygiene, with P values 0,000, Based on the socioecological model, the factor that most influences mother's behavior in fulfilling access to clean water, sanitation and hygiene is at the community level with a tstatistic of 16,789, then at the individual level, the t-statistic is 11,450, the interpersonal factor is t-statistic, 10,804 and the lowest influence is at the level of water facilities. , sanitation and hygiene, so it can be concluded that the existence of facilities in the Pidie community does not really affect the mother's behavior.